1986
DOI: 10.1139/g86-054
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of siliqua strength in Brassica campestris L. I. Studies of F2 and backcross populations

Abstract: KADKOL, G. P., G. M. HALLORAN, and R. H. MACMILLAN. 1986. Inheritance of siliqua strength in Brassica campestris L. I.Studies of F2 and backcross populations. Can. J. Genet. Cytol. 28: 365-373. The inheritance of siliqua strength was studied in Brassica campestris L. using F1, F2, and backcross generations of crosses between cv. Torch (shatter susceptible) and var. Yellow Sarson and var. Brown Sarson (shatter resistant) accessions. Shatter resistance (high siliqua strength) was recessive in all crosses. Crosse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
1
1

Year Published

1989
1989
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 8 publications
2
13
1
1
Order By: Relevance
“…In a subsequent study, Mongkolporn et al (2003) confirmed a phenotypic segregation ratio of 12:3:1 (susceptible: intermediate: resistant) in an F 2 population derived from the Torch x DS-17-D, which indicated two recessive major genes (sh1 and sh2) with dominant epistasis conferring the resistance. This supports the earlier findings of Kadkol et al (1986b). Morgan et al (2000) reported that shatter resistance in B. napus was recessive and mostly determined by additive genes.…”
Section: Inheritance Of Shatter Resistancesupporting
confidence: 92%
See 1 more Smart Citation
“…In a subsequent study, Mongkolporn et al (2003) confirmed a phenotypic segregation ratio of 12:3:1 (susceptible: intermediate: resistant) in an F 2 population derived from the Torch x DS-17-D, which indicated two recessive major genes (sh1 and sh2) with dominant epistasis conferring the resistance. This supports the earlier findings of Kadkol et al (1986b). Morgan et al (2000) reported that shatter resistance in B. napus was recessive and mostly determined by additive genes.…”
Section: Inheritance Of Shatter Resistancesupporting
confidence: 92%
“…Shatter resistance could be improved by introgressing the trait from these types and B. juncea (Kadkol 2009;Raman et al, 2011). Kadkol et al (1986b) considered the genetic variation for shatter resistance within B. napus to be limited and studied inheritance of shatter resistance (measured as siliqua strength) in B. rapa in crosses between Brown Sarson (shatter resistant) and Torch (shatter susceptible) and Yellow Sarson (resistant) and Torch (susceptible). Segregation in the F 2 generation indicated the presence of 2 to 3 recessive genes which showed dominant epistatic interaction controlling shatter resistance.…”
Section: Genetic Variation For Shatter Resistancementioning
confidence: 99%
“…Shatter resistance has been found to be determined by recessive alleles at two or three gene loci which appeared to interact in a dominant epistatic manner (Kadkol et al 1986b). Further biometrical analyses of variation among progenies derived by intercrossing of F 2 plants from the above cross revealed a high level of non-additive genetic variance for all measures of shatter tolerance (Kadkol et al 1986c ).…”
Section: Adaptation To New Management Strategiesmentioning
confidence: 99%
“…One approach is to introduce germplasm from related species by interspecific hybridization. Related species such as Brassica nigra, B. juncea and B. campestris have been used for this purpose [1,17,27] but plants resulting from these crosses are frequently sterile and lose favourable characteristics which have to be regained by back-crossing. This is both timeconsuming and laborious.…”
Section: Introductionmentioning
confidence: 99%